Stem cell and CRISPR/Cas9 gene editing technology in Alzheimer’s disease therapy: from basic research to clinical innovation - He, Cong; Chen, Baojiang; Yan, Ciai; Zhou, Xiaoqing (Frontiers in Genome Editing, 2025)
Alzheimer’s disease (AD), a progressive neurodegenerative disorder characterized by Aβ plaques, tau protein neuronal fiber tangles, and neuroinflammation, poses a significant global health problem, and current therapies focus on the symptoms rather than the cause. This paper gives a new multidimensional therapeutic form to AD treatment by exploring the integrated application of stem cell therapy and CRISPR/Cas9 gene editing technology. The study comprehensively dissected the roles of neural stem cells (NSCs), induced pluripotent stem cells (iPSCs) and mesenchymal stem cells (MSCs) in neural replacement, neuroinflammation modulation and neuroplasticity enhancement, and also explored the application of CRISPR/Cas9 in modifying the pathogenic variants of AD-related genes (APP, PSEN1 and PSEN2). The key findings suggest that gene-edited iPSCs can reduce abnormal Aβ and tau protein accumulation in AD models, improve cognitive function, and provide a platform for disease modeling and drug screening. Stem cell transplantation promotes neurogenesis and synaptic plasticity by secreting neurotrophic factors to improve the brain microenvironment. Despite the challenges of off-target effects, immune rejection, and long-term safety, the synergistic application of these two technologies offers a breakthrough solution for AD treatment. This paper highlights the translational potential of combining stem cells with gene editing technology, which is expected to drive clinical applications in the next 5–10 years. The integration of these advanced technologies not only addresses the limitations of current AD treatments, but also paves the way for a personalized medical approach that is expected to revolutionize the AD treatment landscape and bring new hope to patients worldwide.